Comparison of structural steel lateral force resisting systems for a theoretical hospital grid system - Buell, Grant (Kansas State University, 2009)
In 2006, a research project was being carried out by architects at architecture/engineering firm Cannon Design involving an optimum bay size for a hospital. RISA computer modeling was used to explore a set of lateral force resisting system (LFRS) options for a building based on this optimum bay size and importance category. The structural material was first narrowed down to steel, and then moment frames and braced frames are examined. The LFRS was narrowed down to braced frames, discarding moment frames due to their inordinate story drift. Of the different types of braced frames, the study further narrowed the LFRS system to chevron braced frames. Then the precise arrangement of braces for a particular building size using this bay system was examined. The steel material cost of the final system was compared to a system that only included members sized for gravity loads to demonstrate the rough amount of cost that a lateral system can add to a building.
Keywords: Structural engineering; Lateral forces; Moment frames; Braced frames; Architecture (0729); Engineering, Civil (0543)